2016
DOI: 10.2337/dc16-0383
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Duodenal Mucosal Resurfacing for the Treatment of Type 2 Diabetes: 6-Month Interim Analysis From the First-in-Human Proof-of-Concept Study

Abstract: OBJECTIVETo assess procedural safety and glycemic indices at 6 months in a first-in-human study of duodenal mucosal resurfacing (DMR), a novel, minimally invasive, upper endoscopic procedure involving hydrothermal ablation of the duodenal mucosa, in patients with type 2 diabetes and HbA 1c ‡7.5% (58 mmol/mol) on one or more oral antidiabetic agents. RESEARCH DESIGN AND METHODSUsing novel balloon catheters, DMR was conducted on varying lengths of duodenum in anesthetized patients at a single medical center. RES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
154
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(167 citation statements)
references
References 34 publications
2
154
0
11
Order By: Relevance
“…Indeed, evidence suggests that altered EEC secretion as a consequence of altered nutrient stimulation contributes to the weight-loss and metabolic benefits of bariatric surgery 85 . Similarly, preventing nutrient contact with the duodenal mucosa by placing an endoscopic liner known as Endobarrier 86 , or thermic ablation of the duodenal mucosa 87 , results in improved metabolic profiles hypothetically based on their impact upon EEC functioning. Given the rapid recent advancement in our understanding of EEC biology functional foods or designer drugs aimed at modulating EEC secretion will soon reach clinical practice.…”
Section: Regulation Of Eec Secretion and Nutrient-sensingmentioning
confidence: 99%
“…Indeed, evidence suggests that altered EEC secretion as a consequence of altered nutrient stimulation contributes to the weight-loss and metabolic benefits of bariatric surgery 85 . Similarly, preventing nutrient contact with the duodenal mucosa by placing an endoscopic liner known as Endobarrier 86 , or thermic ablation of the duodenal mucosa 87 , results in improved metabolic profiles hypothetically based on their impact upon EEC functioning. Given the rapid recent advancement in our understanding of EEC biology functional foods or designer drugs aimed at modulating EEC secretion will soon reach clinical practice.…”
Section: Regulation Of Eec Secretion and Nutrient-sensingmentioning
confidence: 99%
“…In this issue of Diabetes Care , Rajagopalan et al (1) present a new therapeutic strategy for treatment of T2D. The strong point of the study is that the authors have developed and studied a novel therapeutic approach in T2D that could elucidate new disease mechanisms involving the role of the duodenum in metabolic regulation.…”
Section: Duodenal Mucosal Resurfacingmentioning
confidence: 99%
“…Various authors have suggested that duodenal bypass 1 ) alters enteroendocrine cell secretion of factors such as glucagon-like peptide 1 (GLP-1), glucose-dependent insulinotropic polypeptide, and peptide YY; 2 ) mediates changes in the gastrointestinal microbiome; or 3 ) produces changes in bile acids that signal through intestinal membrane-bound G-protein–coupled receptors (e.g., TGR5) or hepatocellular farnesoid X receptors with downstream effects on GLP-1 production and secretion of fibroblast growth factors, respectively (5). In the study by Rajagopalan et al (1), DMR was used to prevent nutrient signaling from the duodenum in patients with T2D, and HbA 1c lowering constituted the primary outcome measure.…”
Section: Duodenal Mucosal Resurfacingmentioning
confidence: 99%
See 1 more Smart Citation
“…DMR is a novel, minimally invasive, transoral procedure involving hydrothermal ablation to modify the lining of the duodenum. Recently, an initial study in patients with type 2 diabetes [7] assessed safety and glycaemic indices at 6 months; there was an HbA 1c improvement of 1.2% at the end of follow-up. Another recent publication showed that both glycaemic markers and transaminase levels were improved after this procedure, suggesting potential favourable effects on fatty liver disease as well [8].…”
Section: Introductionmentioning
confidence: 99%